WAJAH ISLAM INDONESIA: Sebuah Tipologi Islam di Jawa Abad 20 - Imam Fawaid; Husnul Khatimah (LP2M Universitas Ibrahimy, 2018)
According to Clifford Geertz, Islam in Indonesia is a religious tradition that is influenced by religious beliefs, ethnic preferences and political ideologies carried out by Modjokuto people as a reflection of the religious traditions of the Javanese community. Geertz states that the style of Islam in Indonesia, especially Java is syncretic Islam. It was from a combination of Islam and Javanese culture. Islam is only a mere accessory but its substance is a noble Javanese culture. Whereas according to Woodward, that religious conception has a big role in transforming certain cultures in this case is Javanese Islamic culture. According to Woodward, the style of Islam in the archipelago is acculturative. It was from the encounter with the local culture in a very long time.